2007
DOI: 10.1300/j094v15n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Physical Activity on Health Status, Pain, and Function in Adults with Fibromyalgia Syndrome

Abstract: Objective: To test the effects of a lifestyle physical activity [LPA] program on health status, pain, fatigue, and function in adults with the fibromyalgia syndrome [FMS]. Methods: Forty-eight sedentary adults with FMS were randomized to either LPA or a FMS education control [FME] group. The LPA participants gradually worked toward accumulating 30 minutes of self-selected moderate-intensity LPA, five to seven days per week. Thirty-four participants [71 percent] completed the study.Results: The LPA group increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 15 publications
2
38
0
2
Order By: Relevance
“…Data from other studies included in this review also report similar or higher increases in PA levels after the intervention [49,50,53,55]. This finding is reflective of evidence from previous studies which suggests that combining pedometer-driven walking programs with goal setting [36,38,60] or cognitive behavioral strategies [57-59] is more effective than pedometer-driven walking alone in adult outpatients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Data from other studies included in this review also report similar or higher increases in PA levels after the intervention [49,50,53,55]. This finding is reflective of evidence from previous studies which suggests that combining pedometer-driven walking programs with goal setting [36,38,60] or cognitive behavioral strategies [57-59] is more effective than pedometer-driven walking alone in adult outpatients.…”
Section: Discussionsupporting
confidence: 75%
“…Three of the studies were conducted in the United States, [49,51,54] while two studies were conducted in Japan [52,55] one was Australian [50] and another study was conducted in Ireland [53]. The total number of participants across the seven studies was 484, with an age range of 40 to 82 years.…”
Section: Resultsmentioning
confidence: 99%
“…Arthritis, joint arthroplasty and fibromyalgia (Table 6) Eight unique studies were identified that presented habitual steps/ day using waist-mounted instruments in individuals with arthritis (Talbot et al, 2003), joint (hip or knee) arthroplasty (Bennett et al, 2008;Goldsmith et al, 2001;Schmalzried et al, 2000;Silva et al, 2002;Silva et al, 2005), a combination of arthritis and arthroplasty (Ono et al, 2007), or fibromyalgia (Fontaine and Haaz, 2007). The median expected value for individuals with arthritis was 4086 steps/ day and for those with joint arthroplasty it was 4892 steps/day.…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
“…2 The primary symptom of FMS is widespread pain, typically associated with persistent fatigue and muscular weakness. As symptoms are often aggravated by a sedentary lifestyle and poor physical condition, along with the use of such antidepressants as selective serotonin reuptake inhibitors and cognitive behavioral therapy, physical activity is considered one of the 3 most evidence-based treatment approaches 3,4 According to the latest reviews of the effects of physical exercises programs on FMS, aerobic exercise programs have proven to be effective in reducing pain, fatigue, and the number of tender points (TPs), 5,6 whereas progressive strength training has proven to decrease the impact of the syndrome on the neuromuscular system, perceived symptoms, and functional capacity. 7 Despite the beneficial effects of different exercise training programs on FMS, very few studies have assessed the effectiveness of a program of physical activity based specifically on flexibility training.…”
mentioning
confidence: 99%